2000
DOI: 10.1002/1521-3773(20000915)39:18<3261::aid-anie3261>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The Dimerization of Chiral Allenes: Pairs of Enantiomers and Pairs of Homomers Furnish Different Diastereomers

Abstract: Treatment of the pure enantiomer 1 with methyllithium furnishes via cycloallene 2 its dimer 3 with high selectivity. In contrast, racemic 1 yielded only 5 % of 3 and 95 % of the cis isomer of 3. Thus, racemic 2 is an example of molecular recognition of remarkable selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
3
20
1
Order By: Relevance
“…Other examples are provided by the thermolysis of the 1,2‐bismethylenecyclobutane derivatives produced at low temperatures upon dimerisation of triphenylallene20 and 1‐(2,2′‐biphenylylen)‐3‐phenylallene 17. Heretofore, only one case has been documented that describes the isolation of a primary product resulting from the attack of a radical centre of a phenyl‐substituted tetramethyleneethane diradical at the phenyl group of the second molecule half, that is, the dimer 20 of racemic 1‐phenyl‐1,2‐cyclooctadiene ( 19 ), which was generated from racemic 8,8‐dibromo‐1‐phenylbicyclo[5.1.0]octane ( 18 ; Scheme ) 16. 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are provided by the thermolysis of the 1,2‐bismethylenecyclobutane derivatives produced at low temperatures upon dimerisation of triphenylallene20 and 1‐(2,2′‐biphenylylen)‐3‐phenylallene 17. Heretofore, only one case has been documented that describes the isolation of a primary product resulting from the attack of a radical centre of a phenyl‐substituted tetramethyleneethane diradical at the phenyl group of the second molecule half, that is, the dimer 20 of racemic 1‐phenyl‐1,2‐cyclooctadiene ( 19 ), which was generated from racemic 8,8‐dibromo‐1‐phenylbicyclo[5.1.0]octane ( 18 ; Scheme ) 16. 21…”
Section: Resultsmentioning
confidence: 99%
“…The first two steps from 2 en route to 16 and 17 should be analogous to the pathway proposed for the conversion of 19 into 20 16. 21 Thus, two molecules of 2 should combine to give the tetramethyleneethane diradical 21 , which then does not undergo the standard reaction of such species with formation of a 1,2‐bismethylenecyclobutane derivative,1 but collapses by bond formation of a phenyl‐bearing allyl‐radical terminus with the phenyl group of the second molecule half furnishing the 1‐methylene‐2,4‐cyclohexadiene derivative 22 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we have observed that under neat conditions, 1,3‐diphenyl allene 7cea undergoes cyclodimerization even at 25 °C in 24 h. Thus, whereas the freshly prepared pure chiral allene 7cea sample exhibits an [ α ] D 25 = –830 ( c = 0.53, CHCl 3 ), the value becomes zero when the product was kept at 25 °C for 72 h. The 13 C NMR spectrum of the product mixture indicates the presence of the cyclodimerized products 16e. We have also found that when freshly prepared pure chiral 1,3‐diphenylallene 7cea was stored in CDCl 3 solution, new signals corresponding to the cyclodimerized products started appearing in the 13 C NMR spectrum in 24 h at 25 °C 17…”
Section: Resultsmentioning
confidence: 82%
“…Indeed, the mechanism of sequential formation of these isomers has been rationalized in terms of homolysis of the C(3)eC(4) bond in 2 to generate a tetramethylene-ethane diradical, which can exist in three isomeric forms: endo,endo, endo,exo and exo,exo, where endo and exo refer to the orientations of the phenyl substituents relative to the two allyl fragments, as depicted in Scheme 2. 8 Now, following the allene dimerization mechanism proposed by Christl, 13 conrotatory ring closure of the endo, endo form leads to the trans isomer 3, while at successively higher temperatures exo,endo and exo,exo diradicals lead to the cis and trans products 4 and 5, respectively.…”
Section: Introductionmentioning
confidence: 84%